Strategi Kerja Sama Sekolah dengan Lembaga Luar Negeri untuk Mengoptimalkan Pelaksanaan Pembelajaran Bahasa Asing di SMA - Anisatussholihah, Nur; Ulfatin, Nurul; Juharyanto, Juharyanto (Universitas Negeri Malang, 2024)
Abstract: This research aims to describe the school's cooperation strategy with overseas language institutions, including the background and work programme, management process, human resources, funding, management optimisation strategies and results. This research uses a qualitative approach with a case study method design. The research visited the site of SHS 1 Malang. Data were collected using interviews, observations, and documentary studies. Data validity checking techniques include observation/observation persistence, triangulation, member checking, complete report writing, and audit tracing techniques. Data analysis is carried out interactively from data collection to conclusion drawing. Results of this study are summarized: (1) The chosen cooperation institution is PASCH in Germany, because it matches the background of the school which provides a language programme, there is a German language teachers, language classes are large and prominent, and supported by adequate school infrastructure; (2) Cooperation programmes include programmes for teachers, students, and facilities; (3) the management process includes planning, implementation, and evaluation in each type of activity; the human resources involved come from PASCH and from the school; programme funding comes from the German Ministry of Foreign Affairs, the school, and students; (4) strategies for optimising cooperation management include the obligation of grade 10 to choose one extracurricular foreign language, optimising human resources, funding, management processes, consistency of cooperation, and utilisation of facilities obtained; and (5) Results of the strategy include continued cooperation, active involvement, more students learning German and being active in activities, increased students competence and achievement, and more students interested in German language learning and programmes.Keywords: school cooperation, foreign language institute, learning Abstrak: Penelitian ini bertujuan mendeskripsikan strategi kerja sama sekolah dengan lembaga bahasa di luar negeri, mencakup latar belakang dan program kerja, proses pengelolaan, sumber daya manusia, pendanaan, strategi optimalisasi pengelolaan dan hasilnya. Penelitian ini menggunakan pendekatan kualitatif dengan rancangan metode studi kasus. Lokasi penelitian di SMAN 1 Malang. Data dikumpulkan melalui teknik wawancara, observasi, dan studi dokumenter. Teknik pengecekkan keabsahan data berupa ketekunan observasi/pengamatan, triangulasi, pengecekkan anggota, penulisan laporan yang lengkap, serta teknik penelusuran audit. Analisis data dilakukan secara interaktif mulai dari pengumpulan data sampai dengan penarikan simpulan. Hasil penelitian ini telah dirangkum: (1) lembaga kerjasama yang dipilih adalah PASCH di Jerman, karena sesuai dengan latar belakang sekolah yang menyediakan program bahasa, terdapat guru bahasa Jerman, kelas bahasa tergolong besar dan menonjol, serta didukung infrastruktur sekolah yang memadai; (2) program kerja sama meliputi program untuk guru, peserta didik, dan fasilitas; (3) proses pengelolaan meliputi perencanaan, pelaksanaan, dan evaluasi di setiap jenis kegiatan; SDM yang terlibat berasal dari PASCH dan dari sekolah; pendanaan program bersumber dari Kementerian Luar Negeri Jerman, sekolah, dan peserta didik; (4) strategi optimalisasi pengelolaan kerja sama mencakup kewajiban kelas 10 memilih satu ekstrakulikuler bahasa asing, pengoptimalan SDM, pendanaan, proses pengelolaan, konsistensi kerja sama, dan pemanfaatan fasilitas yang diperoleh; dan (5) hasil strategi berupa kerja sama yang berlanjutan, keterlibatan aktif, semakin banyak peserta didik yang mempelajari bahasa Jerman dan aktif dalam kegiatan, peningkatan kompetensi dan prestasi peserta didik, dan semakin banyaknya peserta didik yang tertarik dengan pembelajaran dan program bahasa Jerman.Kata kunci: kerja sama sekolah; lembaga bahasa asing; pembelajaran